Analisis Teknikal Pergerakan Saham PT Bank Jago Tbk dengan Menggunakan Indikator Candlestick dan Moving Average Convergence Divergence - Andi Farhan; Tjetjep Djuwarsa; Radia Purbayati (Indonesian Journal of Economics and Management, 2022)
This study aims to determine the movement of shares of PT Bank Jago Tbk for the period January 1 – May 20 2022 using candlestick indicators and Moving Average Convergence Divergence (MACD), this study focuses on the economic aspect. The method used is descriptive method. The type of data used is qualitative data. The source of data used is secondary data obtained from charts on tradingview.com tools. Referring to the results of the analysis that has been carried out, the movement of PT Bank Jago Tbk's shares shows a decline (downtrend) using both candlestick and MACD indicators. This indicates that market participants should take a sell action.